2019
DOI: 10.1080/02626667.2019.1609682
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of flood-model calibration using single and multiple events

Abstract: Lack of discharge data for model calibration is challenging for flood prediction in ungauged basins. Since establishment and maintenance of a permanent discharge station is resource demanding, a possible remedy could be to measure discharge only for a few events. We tested the hypothesis that a few flood-event hydrographs in a tropical basin would be sufficient to calibrate a bucket-type rainfall-runoff model, namely the HBV model, and proposed a new event-based calibration method to adequately predict floods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…More conceptual approaches that aim to overcome this issue by minimizing or even avoiding the use of additional data for calibration have been discussed in previous research (Gharari et al, 2014; Hulsman et al, 2018; Kapangaziwiri et al, 2012; Li et al, 2014). Such approaches suggest new methods to make use of insufficient data sources by, for example, using water level measurements (Hulsman et al, 2018; Jian et al, 2017) or discontinuous observational time series (Reynolds et al, 2019). More conceptual approaches use relational constraints based on export knowledge to specify the parameter space (Gharari et al, 2014) or to constrain hydrological model output and the parameter space based on, for example, the Budyko framework (Budyko, 1974; Bouaziz et al, 2018; Kapangaziwiri et al, 2012; Li et al, 2014).…”
Section: Motivationmentioning
confidence: 99%
“…More conceptual approaches that aim to overcome this issue by minimizing or even avoiding the use of additional data for calibration have been discussed in previous research (Gharari et al, 2014; Hulsman et al, 2018; Kapangaziwiri et al, 2012; Li et al, 2014). Such approaches suggest new methods to make use of insufficient data sources by, for example, using water level measurements (Hulsman et al, 2018; Jian et al, 2017) or discontinuous observational time series (Reynolds et al, 2019). More conceptual approaches use relational constraints based on export knowledge to specify the parameter space (Gharari et al, 2014) or to constrain hydrological model output and the parameter space based on, for example, the Budyko framework (Budyko, 1974; Bouaziz et al, 2018; Kapangaziwiri et al, 2012; Li et al, 2014).…”
Section: Motivationmentioning
confidence: 99%
“…The events above both thresholds were selected within the period between June 2000 and December 2011. The length of the events was defined as in Reynolds et al (2019). The start of each flood event was the time step at which the precedent rainstorm started, while its end was when the percentage change in the recession decreased by less than 5% for 10 consecutive hourly time steps, or when the percentage change was positive because of the occurrence of a new rainfall event.…”
Section: Study Sitementioning
confidence: 99%
“…Performing field measurements including periods representative of the main hydrological processes could be another option to overcome the lack of discharge data for model calibration Beven 2009, Reynolds et al 2019). In an earlier study (Reynolds et al 2019), we tested the hypothesis that a few highflow events would be sufficient to calibrate a bucket-type rainfallrunoff model and our results indicate that two to four events, compared to the scenario of not having any data, could considerably improve flood predictions with regard to accuracy and uncertainty reduction. These results were encouraging, but the events used in calibration were above an extreme threshold (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…These were events that generated a streamflow over 211 m 3 /s. This streamflow threshold was defined following the methodology proposed by Reynolds et al [30], using the annual minimum from monthly from monthly maximum records instead of the annual mean. This obeyed the short time-series available for the streamflow (1 year; Figure 2).…”
Section: Datamentioning
confidence: 99%
“…In the absence of long-term observations, event sampling data may provide sufficient information to perform hydrological and hydrodynamic simulations. In this sense, several studies have found that the degree of hydrological information obtained by processing data from several storm events is comparable to that obtained by processing long-term data series [30][31][32][33][34][35][36]. The implementation of externally coupled models with event sampling data for flood hazard assessment may be quite relevant in zones with high spatial precipitation variability such as those located in the Andes-Amazon transition [37], where monitoring networks are sparse and recently established.…”
Section: Introductionmentioning
confidence: 96%